Analysis of the Effect of Capital, Labor, Raw Materials, Length of Business, and Location on MSMEs Income in the Food and Beverages Industry Sector (A Case Study on Home Industry Assisted by the Cooperatives and MSMEs, East Bekasi Districts) - Laurencia, Sharen (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
East Bekasi District has the most significant number of Micro, Small and Medium Enterprises (MSMEs) accompanied by the Bekasi City Cooperatives and MSMEs Office. The food and beverage sector is the largest group compared to others. MSME faces capital difficulties and sales that have yet to be maximized. However, this kind of business is widely carried out considering the convenience and promising market potential. This study aims to determine the variables of capital, labour, raw materials, length of business, and location on the income of MSME actors assisted by the Cooperatives and MSMEs in Bekasi City research is quantitative research. The population in this study were food and beverage MSMEs assisted by the Bekasi City Cooperatives and MSMEs, as many as 145 MSME actors. The sample used was 60 business actors using a simple random sampling technique. The analytical method used is Ordinary Least Square (OLS) using SPSS. The results of this study indicate a positive and significant effect of capital, labour, raw materials, length of business, and location on the income of MSME actors. Capital is the most influential variable on income. The independent variables jointly affect the income of food and beverage MSME actors by 69.7 per cent.